The matricellular protein CYR61 interferes with normal pancreatic islets architecture and promotes pancreatic neuroendocrine tumor progression - Huang, Yu-Ting (Oncotarget, 2015)
The significance of matricellular proteins during development and cancer progression is widely recognized. However, how these proteins actively contribute to physiological development and pathological cancer progression is only partially elucidated. In this study, we investigated the role of the matricellular protein Cysteine-rich 61 (CYR61) in pancreatic islet development and carcinogenesis. Transgenic expression of CYR61 in β cells (Rip1CYR mice) caused irregular islets morphology and distorted sorting of α cells, but did not alter islets size, number or vascularization. To investigate the function of CYR61 during carcinogenesis, we crossed Rip1CYR mice with Rip1Tag2 mice, a well-established model of β cell carcinogenesis. Beta tumors in Rip1Tag2CYR mice were larger, more invasive and more vascularized compared to tumors in Rip1Tag2 mice. The effect of CYR61 on angiogenesis was fully abrogated by treating mice with the anti-VEGFR2 mAb DC101. Results from in vitro assays demonstrated that CYR61 modulated integrin α(6)β(1)-dependent invasion and adhesion without altering its expression. Taken together, these results show that CYR61 expression in pancreatic β cells interferes with normal islet architecture, promotes islet tumor growth, invasion and VEGF/VERGFR-2-dependent tumor angiogenesis. Taken together, these observations demonstrate that CYR61 acts as a tumor-promoting gene in pancreatic neuroendocrine tumors.